ENT 600 : Sarjana Auto Garage / Josue Blasius ...[et al.] - Blasius, Josue; Wahid, Muhammad Azizi; Sapuan, Muhammad Amirul; Mohd Noor, Muhammad Hafizan (2019)
Auto Sarjana Garage is workshop intent to help the people around Puncak alam regarding their car. This workshop consists of two main activities which is servicing and repairing car. This workshop also functions as a place for the people around Puncak Alam to ask any advice regarding the problems of their cars. The workshop is located at the Alam Suria in the edge of this town. Before the workshop is start their operation, some observation is take into account to determine the most type of car used in this town. This workshop and its services were discussed further in the following chapters.